REPRESENTASI KARAKTERISTIK LOKAL MASYARAKAT NELAYAN KAMPUNG LAUT : ANALISIS UNTUK PENGEMBANGAN MASYARAKAT PESISIR - Waluyo Handoko (Fakultas Ilmu Sosial dan Ilmu Politik, 2011)
Policy development of marine and coastal communities that are uniformly regarded as one of the causes of the failure of poverty alleviation programs. Up to this moment, fishing community empowerment programs in Kampung Laut no one has managed to lift the quality of life for sustainable fishing. Therefore, this research shows that people in Kampung Laut has the characters tend to be hard, lazy and not work hard. When the silting caused by sedimentation exist, it is not easy to find other business alternatives because of the existence of these three bad characteristics. Even worse, Kampung Laut communities have gambling habit. These characteristics really need the presence of community leaders such as formal leaders, religion, customs, youth entrepreneurship and motivator to lead and mobilize the community together to move forward. In addition, community empowerment programs should be coordinated across sectors, either by department or governmental agency or community organization. Development program should also make the most of the existing economic potential, and involving both men and women fishers of Kampung Laut.